Al-malik al-salih – Islam and the monarchy in 1930s Egypt. Issue 3 (26th April 2022) - Tripp, Charles
Abstract: This article examines the significance of and the motives behind the projection of a distinctively Islamic image of King Faruq of Egypt in the years that followed his ascent to the Throne in 1936. It argues that the creation of the persona of al-malik al-salih (the righteous king) was one aspect of the strategy developed by Ali Mahir Pasha (Prime Minister and then Head of the Royal Diwan) to safeguard the monarchy in an era of mass politics. The campaign, however, took on a life of its own, obliging Ali Mahir to reassert control over the image of the 'righteous king'.